Financial Performance and Corporate Value Relationship: Does Good Corporate Governance Matter? - Lestari Adhi Widyowati; Inta Hartaningtyas Rani (Quantitative Economics and Management Studies, 2022)
This study was conducted through moderating regression analysis to determine the effect of financial performance on firm value with good corporate governance as a moderating factor. The dependent variable in this study is firm value, represented by stock prices. The independent variables in this study are financial performance (as proxied by ROE and DAR), and the moderating variable is good corporate governance (GCG), as proxied by institutional ownership. The study was based on 193 manufacturing companies' financial statements on the Indonesia Stock Exchange from 2019 to 2020. The ROE and DAR variables were found to impact stock prices. Institutional ownership as a moderator is proven to strengthen the influence of ROE on stock prices while weakening the relationship of DAR to stock prices. In this study, all hypotheses tested were accepted. This study fills a knowledge gap about the role of institutional ownership in moderating financial performance and firm value. The proxy chosen to represent the variables in this study will add novelty to the empirical research and provide a further management perspective.